Examining Bisexuality in Saccage by Eric Jourdan, Call Me by Your name by Andre Aciman, and Un Garçon comme une Autre by Joël Breurec: An Anthropological Approach - Sukwichai, Pariwat (Journal of Arts and Thai Studies, 2023)
Objectives: In contemporary LGBT studies, bisexuality remains rarely explored compared to other sexual identities. This article aims to investigate bisexuality, specifically in literature where it continues to be shadowed by gay and lesbian representations despite the burst of LGBT literature throughout the last few decades. It also emphasizes the universal aspect of bisexual experiences and practices which transcend national boundaries through a comparative study of literary works from different linguistic and cultural backgrounds, while remaining conscious to the particularities of each social and cultural context. Methods: In an attempt to broach bisexuality in literary studies, the necessity to look to social sciences is unavoidable despite their markedly different approaches and methods. Therefore, the question is how can we articulate between knowledge from other disciplines and the apprehension of bisexuality in literary works without putting aside the nature of literature: literariness. In this difficulty, anthropological approaches prove adequate in allowing literature to interrogate extra-literary questions, making use of knowledge from other disciplines while simultaneously putting forward its literary aspects, since literature and anthropology share the same tool: writing or composing. The anthropological approaches used in this study – imagery, gaze, and bodily pleasure – are conjugated with literary strategies and techniques in the analysis of three contemporary French and American novels – Saccage (2006) by Eric Jourdan, Call Me by Your Name (2003) by André Aciman, and Un Garçon comme une Autre (2013) by Joël Breurec. Results: The results of this research show that knowledge in social sciences, though essential, is insufficient in grasping bisexuality represented through literary works. The use of anthropological approaches helps us grasp bisexuality both as human practices and experiences, and as a subject for literary creation, which shed light on the construction and legitimacy of this sexual identity. Application of this study: This study contributes to literary research and gender studies by emphasizing the necessity of interdisciplinarity in thinking sexuality in literature, and provides one possible approach to do so without losing sight of the particularities of literature and what it can do.